Opportunities and Challenges of Theological Education and Missional Formation in the 4IR: A Paradigm Shift - Knoetze, Hannes (Transformation, 2023)
In discussing the opportunities and challenges of theological education within a ‘glocal’ context, which in the context of this article is focussing on Africa, African Traditional Religions, other living faiths, post-Christendom, illiteracy, traditionalism, secularisation and the Fourth Industrial Revolution (4IR), are all part of a paradigm shift. Addressing this paradigm shift, the article will at least address the following three issues. First, the re-examining of some methodological aspects of our curriculums. The second aspect I would call human- (student and educator) centred awareness, or it can also be called ‘knowledge-constitutive interest’. The third aspect of theological education has to do with the fact that theological education does not take place ‘out there’ but is a life transforming and very personal issue that has to do with praxis, a way of life.